Manifestasi Okular pada Pasien dengan Lupus Eritematosus Sistemik (SLE) - Anugrahsari, Santi; Dila Sandy, Marcelia Nova; Yuningsih, Wulan; Sharen (Jurnal MedScientiae, 2026)
Systemic Lupus Erythematosus (SLE) is a multisystem autoimmune disease with a wide range of clinical manifestations, including ocular involvement. Ocular manifestations in SLE can affect both the anterior and posterior segments and are significantly associated with systemic disease activity. This review aims to comprehensively examine current scientific literature related to ocular manifestations in SLE patients, including the clinical spectrum, diagnostic modalities, correlation with systemic disease activity, and the impact of therapeutic toxicity, particularly hydroxychloroquine. A systematic literature review was conducted based on 30 peer-reviewed scientific articles published within the past five years. Inclusion criteria included English-language publications involving diagnosed SLE patients with ocular involvement. Articles were analyzed based on the type of ocular manifestation, diagnostic methods, association with systemic parameters, and the imaging technology employed. The most commonly reported manifestations were lupus retinopathy, retinal vasculitis, keratoconjunctivitis sicca, and hydroxychloroquine-induced maculopathy. Advanced imaging modalities such as Optical Coherence Tomography (OCT) and Optical Coherence Tomography Angiography (OCTA) played a key role in detecting retinal involvement, even at subclinical stages. Hydroxychloroquine toxicity remains a major concern, especially in patients with systemic risk factors and inadequate retinal monitoring. Ocular involvement in SLE serves as a valuable diagnostic and prognostic indicator. Early detection and regular monitoring using advanced imaging technologies are essential strategies to prevent irreversible vision loss and assess lupus systemic activity. A multidisciplinary approach involving both rheumatologists and ophthalmologists is crucial in the holistic management of SLE patients.